Agricultural management affects earthworm and termite diversity across humid to semi-arid tropical zones - Ayuke, Fredrick O.; Pulleman, Mirjam Margreet; Vanlauwe, Bernard; Goede, Ron G.M. de; Six, Johan; Csuzdi, C.; Brussaard, Lijbert (Elsevier, 2011)
Earthworm and termite diversity were studied in 12 long-term agricultural field trials across the sub-humid to semi-arid tropical zones of Eastern and Western Africa. In each trial, treatments with high and low soil organic C were chosen to represent contrasts in long-term soil management effects, including tillage intensity, organic matter and nutrient management and crop rotations. For each trial, a fallow representing a relatively undisturbed reference was also sampled. Earthworm taxonomic richness decreased in the direction fallow > high-C soil > low-C soil and earthworm abundance was higher in fallow than under continuous crop production. Termite abundance was not significantly different between fallow and high and low-C treatments and termite taxonomic richness was higher in fallow soil than in the two cropping systems. We concluded that fewer species of earthworms and termites were favored under agricultural management that led to lower soil C. Results indicated that the soil disturbance induced by continuous crop production was more detrimental to earthworms than to termites, when compared to the fallow.